Ritmos biológicos na emergência de Cercárias de Shistosoma mansoni Sambon, 1907 (Platyhelminthes: Digenea) em infecções mono e plurimiracidianas de Biomphalaria glabrata (Say, 1818) (Mollusca: Gastropoda) - Bogéa, Tami Helena Pestana (1992)
This work aims to study the daily rhythm of emergence of S. mansoni cercariae in mono - and plurimiracidial infections of B. glabrata. For this purpose the emergence at daytime and nighttime and its peaks were compared through a chronobiological methodology. For the tests,19 and 37 specimens of B.glabrata (Belo Horizonte, MG) infected respectively with one and five miracidia of sympatric schistosome were kept at outdoor conditions. Other observations included the estimations of the infection rate, the pre-cercarial period,the survival of infected snails, and the number of emerged cercariae at each 24-h intervals.The correlation between air temperature and the number of emerged cercariae was also investigated. Most cercariae emerged at daytime (from 6 a. m. to 6 p. m.) for both miracid ial doses. Thus, 96. 3% of the cercariae ernerged in this phase in rnonorniracidial infections and 9 4. B% in the plurimiracidial ones. The daily peaks of cercarial emergence did not differ signi ficantly between mono- and plurimiracidial infections. In most snai ls, the cercaria! emergence showed 24-h rhythms of the with acrophases between 2 p.m. and 5 p.m. cercariae emerged at daytime, some did it Although most at nighttime (3. 7% in the mono- and 5. 2% in plurimiracidial infections). In two snails more than 30% of the cercaria! emergence occurred during this phase. This pattern is possibly associated to some crepuscular or nocturnal activities of the vertebrate hosts or even to some infection procedures in the laboratory. Future studies concerning the investigation of this temporal pattern in S. mansoni stra ins just isolated from the field should be encouraged. The rhythm of S. mansoni cercar i a! emergence is cons idered to be a gated rhythm s ince the cercar iae seem to "wa it" for some environmental s ignal 1n order to emerge. The adapt ive importance of the synchrony in cercar ia! emergence refers to better chances of these larval forms to infect the vertebrate hosts. Future stud ies concern ing the d ifferent iat ion between product ion and emergence rhythms would make it poss ible to know whether the cercariae emerge as they are produced or not. The pre-cercar ial period. the survival of infected sna ils ana the number of emerged cercar iae per sna il at each 24 h interval did not differ signif icantly between mono- and plur im irac idial infections. The infection rates were higher in pluri- than in monom irac id ial infections. T he var iat ions in these parameters could be due to paras ite infect ivity and/or sna il suscept ib ility differences. Future work s hould also evaluate poss ible short-term mod if icat ions due to some laboratory procedures cercarial involving both the r.mail and paras ite samples. The emergence was not s istemat ically assoc iated to var iat ions in the a ir temperatura.